Strengthening Religious Moderation in Social Media to Fight Online Radicalism - Sulhi Muhammad Daud; M. Iqbal Bafadhal (MKWK PAI Universitas Jambi, 2023)
The aim of this research is to explore how efforts to strengthen religious moderation on social media can eradicate online radicalism. The author uses the Maudhu'i exegesis method, namely raising one topic then selecting several verses and hadiths related to religious moderation then connecting them with developments in technology, the internet and social media. The research results show that the use of counter-narrative material on social media will encourage religious moderation, tolerance, a spirit of pluralism, harmony and peace, so that the phenomenon of online radicalism can actually still be resisted by the younger generation. The way to do this is by strengthening religious moderation on social media such as; social media campaigns accompanied by collaboration with influencers, preaching religious moderation through podcasts, and creating innovative playstore-based religious moderation applications on smartphones.